TINDAK TUTUR DIREKTIF GURU DAN RESPON SISWA DALAM PEMBELAJARAN BAHASA INDONESIA DI KELAS VII SMP NEGERI 2 PAINAN - Yaditta, Puji Detty; Manaf, Ngusman Abdul; Noveria, Ena (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACT The purpose of this study was to describe the shape, strategy, and the context of use of personality strategies responded positively and negatively by the student in the learning process in class VII SMP Negeri 2 Painan. The research is a qualitative research with descriptive methods. The data in this study of speech acts teacher and student response to the learning process. The technique used for data collection is a recording technique. Based on the findings of research and discussion, we can conclude the following. There are four forms of speech acts directive used by teachers in the learning process, which ordered directive speech act, advise, demanding, and challenging. The fourth form of speech acts directive is spoken by using four strategies recalled, that speak frankly without further ado, speak frankly with the preamble of politeness positive, speak frankly with the preamble of politeness negative, and recalled vague in the context of the process learning and different atmosphere. Teacher’s speech act get a different response from the students. The response given students verbal response can be positive, negative verbal, nonverbal positive and negative nonverbal Kata kunci: tindak tutur guru, respon siswa, proses pembelajaran